Experimental and theoretical study of the restrained shrinkage cracking of early age well cement. (30th November 2020) - Zhang, Yige; Li, Linfei; Xi, Yunping; Hubler, Mija
Highlights: The digital image correlation (DIC) method is proposed to measure the strain development and cracking distribution during early phase change of well cement. The sequential hydration – drying shrinkage – cracking of early age well cement under restrained ring conditions are captured experimentally and theoretically. The theoretical model describes the stress distribution and cracking development times in the hydrating well cement sheath. Insights are presented on the key material and geometric parameters which control the fracture of a well cementing structure. Abstract: The shrinkage cracking occurring in oil & gas well cement material is a major factor that reduces the cement sheath integrity and impairs the durability of an underground well. Shrinkage mainly takes place in the early hydration period of the cement, and the resulting restrained shrinkage cracking can form a leaking network for oil & gas or carbon dioxide stored in an underground reservoir. It is thus important to understand the early age behavior of well cement and the leaking pathway formation in the well. This study describes the application of the digital image correlation (DIC) method as a tool to measure the strain development and crack distributions of well cement in the lab during early phase changes. A theoretical model is presented to calculate the stress distribution built up in the cement sheath during early ages of well cement hydration, which helps to interpret the experimental observations and determine the major factors influencing the cracking sequences. This study presents the whole hydration – drying shrinkage – and cracking mechanism of early age well cement under restrained ring conditions experimentally and theoretically. The results offer useful insights on the key material and geometric parameters which control the fracture of a well cementing structure.